(untitled) (American Journal of Islam and Society, 1989)
In recent years there has been numerous Islamic publications in both social and economic fields trying to establish their theoretical and empirical basis according to Islamic principles Modelling Interest-Free Economy, A Study in Macro-economics and Development by Dr. Muhammad Anwar is one book which is a laudable study in economics, applying particularly the mudaraba system to the macro-economic level. Although it is really valuable study, I would like to express my opinions on the following points. 1) Regarding the technical points, it would have been useful for the reader if the sources used as reference had been given as footnotes. It is difficult to refer back to the sources. 2) “Muslim countries are reforming their financial systems in the light of Islamic teachings. Islamic financial institutions conduct their operations in ways that steer clear of interest and conform to the Sharia, the Islamic code of law and ethics (p. 7).” In such studies, it would be useful to draw a clear line between trade activities and partnerships and the banking system. Since Islamic countries and Muslim scholars are just now trying to develop a new banking system according to Islamic principles, we should be strictly careful when using the term “Islamic Banks.” In contrast with some Muslim scholars, for similar reasons we should also be careful when putting forward the mudaraba system as the basis for a banking or economic system. Instead of calling these institutions “Islamic” it would be more proper to use such terms as “Interest-Free Commercial Institutions”, “Interest-Free Financial Institutions”, “Interest- Free Credit Institutions (Corporations) ,” etc. 3) The mudaraba contract as a form of partnership is directly related to trading activities. The involvement of the banking system in trade activities by establishing partnerships with certain firms through mudaraba contracts can severely distort the free competition in the market system which is encouraged by the Prophet (SAAS). Banks are institutions in which huge amounts of financial resources are accumulated. As the banks enter the market to make commercial transactions, even though in the forms of mudaraba, musharaka or murabaha, this involvement will likely ...